Overview of The Application of Astronomical Science in The History of Islamic Civilization and The Relationship with Architecture - Juharida, Azzah; Agustiananda, Putu Ayu P; Santosa, Revianto Budi (Departement of Architecture, Universitas Islam Indonesia, 2025)
The development of astronomy in the golden age era began with the discovery of astrolabes and predicting lunar and solar eclipses, the movement of stars, prayer times, determining the calendar system, and determining the direction of the Qibla. From these discoveries, knowledge about Qibla direction determination technology developed from time to time. The history of determining the direction of Qibla in Indonesia, especially in Yogyakarta, has its pros and cons in its implementation. The renewal figure was KH Ahmad Dahlan who was the pioneer of the Qibla direction based on astronomical calculations. This research was conducted at Langgar Kidoel KH Ahmad Dahlan Yogyakarta, which was the first Muslim place of worship to apply an astronomical system in determining the direction of the Qibla in Indonesia. This study aims to determine the application of astronomy in the history of Islamic civilization and its relation to architecture. The results of the study show that astronomy is very influential in the field of architecture, namely in determining the direction of the Qibla and the cardinal directions which have an impact on the design of the orientation of the building and the concept of Islamic architecture. In building orientation, the Qibla direction and the cardinal directions are closely related to building physics and building access; while in the concept of Islamic architecture, the direction of the Qiblah and the cardinal directions affect the spatial arrangement in accordance with the Sunnah of the Prophet. Keywords: Architecture; Astronomy; Islamic Architecture; Qibla Direction